Euglycemic diabetic ketoacidosis associated with a sodium-glucose co transporter 2 inhibitor use in a trauma patient: a case report - Ophélie Dirand; Julie Dupont; Emmanuel Weiss; Myriam Lamamri (International Journal of Emergency Medicine)
Abstract Background Sodium-glucose co-transporter 2 inhibitors (SGLT2i), like empagliflozin, are widely prescribed for managing type 2 diabetes mellitus. However, they carry a rare but serious risk: euglycemic diabetic ketoacidosis (EDKA). EDKA’s atypical presentation, characterized by metabolic acidosis and ketosis despite normal blood glucose levels, often delays diagnosis, posing significant challenges in intensive care. Case presentation We report the case of a 74-year-old female with type 2 diabetes on empagliflozin, gliclazide, and metformin. Admitted after severe trauma from a road traffic accident, she subsequently developed EDKA. This was fostered by septic shock due to methicillin-susceptible Staphylococcus aureus cellulitis. All home medications were discontinued. EDKA was successfully managed with fluid volume expansion, continuous intravenous insulin and dextrose infusions, resolving her metabolic derangements within five days. Conclusion SGLT2i use is associated with a significantly increased risk of EDKA. Early diagnosis is critical due to its potential lethal consequences. Reintroducing SGLT2i in ICU patients, especially trauma patients at high sepsis risk, requires careful, daily reassessment given their unpredictable clinical course.